Characterizations on the doping of single-crystal silicon carbide. (December 2022) - Xiong, Huifan; Mao, Weiwei; Wang, Rong; Liu, Shuai; Zhang, Naifu; Song, Lihui; Yang, Deren; Pi, Xiaodong
Abstract: Due to its intriguingly electrical, thermal and optical characteristics, single-crystal silicon carbide (SiC), one of the most significant wide-bandgap semiconductors, has been receiving intense attention. Up to date, SiC has been investigated for applications in high-power and high-frequency electronics, ultraviolet optoelectronics and quantum computing, which all critically have a strict requirement on the doping of SiC. To improve the quality and reliability of SiC devices, the amounts of both intentionally and unintentionally doped impurities as well as the doping-dependent characteristics like resistivity must be characterized with accuracy and convenience. This article reviews these characterization methods, including elemental analysis, electrical and optical methods. Among those, the term "elemental analysis" dominantly introduces the secondary ion mass spectroscopy technique (SIMS). Meanwhile, for the electrical methods, we will discuss the mature techniques used in laboratory including the Hall effect method, the electrical scanning probe techniques, etc. Moreover, the optical methods introduce the optical absorption method, Raman spectra analysis and photoluminescence spectroscopy. Additionally, a focus is placed specifically on the characterization of the carrier concentration distribution in SiC wafer, which meets the practical requirement for in situ diagnostics of SiC wafers. Graphical abstract: Image 1 Highlights: Typical characterization methods for measuring the doping of SiC material are reviewed and compared. Optical methods are considered as good candidates for process monitoring. The advantages and disadvantages of each characterization method are compared and discussed.